TELAAH METODOLOGIS PEMIKIRAN HOLISTIK TRANSFORMATIF: POLA DAN DASAR PEMIKIRAN TERHADAP AL-QURAN SEBAGAI PETUNJUK HIDUP UMAT MANUSIA - Ayat Dimyati (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2015)
The scientific activity of the experts should be shifted from the perceived partiality of science. It was offered as a continuation of the existing mindset and used in every scientific movement after perceived no longer sufficient when faced with the problems of life today. In helping the understanding to find the truth of the obtained designations think. There are two ways of thinking are built, including ways of thinking deductive and inductive thinking. Al-Quran and al-Hadith as the primary sources of Islamic law, which mean that the people will straighten out their life or solving their problems through the replace and repayment that to them. Textually, both sources have been fixed and will not change, whereas the activities of life are constantly changed. The instrument will connect continuesly between fixed and changed in the pattern of thought development. To explore this thought pattern, it must be done through a social sciences and anthropology approaches which are very well known as the quantitative and qualitative approaches. Islam has to be seen as rahmatan lil ‘alamin which cannot be aimed without the truly thought and action both manhaji and ‘irfani. In the past, it is called as syir’ah thought (contextual and textual).